European electricity deregulation will not level the playing field. - Jancher, L.
The European Commission (EC) announced on 12 March 2001 a new directive for the electricity markets of its member states: all should be fully open to competition by January 2003. That is, all consumers, whether industrial or residential, in any nation in the European Union (EU), should be free to choose an electricity supplier. Here, the author argues that, while this seems an affirmation of free and open competition, many state-owned electric utilities will be insulated from competition by the decision. He believes that it will prevent a level playing field from ever taking shape
Keywords: Europe; European Commission directive; European Union; Competition; Electricity deregulation; Electricity supplier; State-owned electric utilities